Adelmann of Liège and the Eucharistic Controversy. With a Musicological Study of the “Rhytmud alphabeticus” - Geybels, Hans (Dallas Medieval Texts and Translations, 2013)
With a Musicological Study of the “Rhytmud alphabeticus” by Pieter Mannaerts
Keywords: undefined